2009
DOI: 10.1175/2008jamc1817.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Lightning, Precipitation, and Hydrometeor Characteristics over the North Pacific Ocean*

Abstract: Lightning data from the Pacific Lightning Detection Network (PacNet) and Lightning Imaging Sensor (LIS) on the Tropical Rainfall Measuring Mission (TRMM) satellite were compared with TRMM precipitation radar products and latent heating and hydrometeor data. Three years of data over the central North Pacific Ocean were analyzed. The data were divided into winter (October-April) and summer (June-September) seasons. During the winter, the thunderstorms were typically embedded in cold fronts associated with eastwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 74 publications
4
69
0
3
Order By: Relevance
“…There are no previously published results examining the potential relationship between extratropical cyclone occurrence and lightning activity in the Australian region, with very few results presented for other regions of the world (e.g. Market et al 2006, Pessi andBusinger 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There are no previously published results examining the potential relationship between extratropical cyclone occurrence and lightning activity in the Australian region, with very few results presented for other regions of the world (e.g. Market et al 2006, Pessi andBusinger 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, a domain average profile would likely exhibit considerably lower mixed phase reflectivity. The average height of the near-surface reflectivity bin (i.e., the lowest bin that is free The results of Pessi and Businger [2009a] are included for comparison. Figure 10.…”
Section: ~0mentioning
confidence: 99%
“…Their analysis showed that the temporal distribution of lightning is not well correlated with convective rainfall, while it is well correlated with the simulated concentrations of solid hydrometeors, particularly during the development stage of the storms. Pessi and Businger (2009) explored the relationship between lightning measured from LIS and from a ground network of detectors installed on islands of the North Pacific, and the precipitation and hydrometeor profiles obtained from the TRMM PR. They found a logarithmic increase of flash rates with increase of convective rainfall, as well as of other storm characteristics such as precipitable ice path, radar reflectivity, and storm height, for winter and summer storms in the northern Pacific Ocean.…”
Section: Formenton Et Al: Relationships Between Lightning Activitmentioning
confidence: 99%